Studi Literatur: Herbal Indonesia Berkhasiat Sebagai Anti Hipertensi - Nur asiyah siregar (Program Studi S1 Farmasi, STIKES Senior, Medan, 2023)
Introduction: High blood pressure (hypertension) is often influenced by several factors including age and obesity It can be characterized by an increase in blood pressure on the walls of the arteries. Objective of the research: The purpose of this literature study is to summarize the various types of Indonesian herbal medicines that have antihypertensive effects. Method: The method used to write this article The electronic database indexed by Google Shoolar uses a literature review approach, the inclusion criteria taken based on journals published between 2016-2023. Result: Based on the research results of this review article, it was found that Indonesian shrubs could be an effective alternative therapy for treating high blood pressure (hypertension). Conclusion: We can find Indonesian herbal plants with their properties as hypertension drugs easily around us, such as red guava, turmeric, carrots, aloe vera, green grass jelly, wood sweet, garlic, noni, soursop leaves, avocado leaves, balimbing wuluh, celery, lemongrass, and ginger which can be an alternative treatment that is no less effective as blood pressure lowering hypertension cure.